Urinary incontinence as a main clinical manifestation of early stage Wernicke’s encephalopathy: a case report - He, Haitian; Wang, Kebing; Wang, Yang; Luo, Jinbin (Frontiers in Neurology, 2023)
Wernicke's encephalopathy (WE) is a condition caused by a deficiency of vitamin B1. While there have been many reported cases of WE in the literature, there are few reports on the early stages of the disorder. In this report, we present a case of WE with urinary incontinence as the main clinical manifestation. A 62-year-old female patient was admitted to the hospital due to intestinal obstruction and did not receive vitamin B1 supplements for ten days. Three days after her operation, she developed urinary incontinence. She also had mild mental symptoms, such as a little indifference. After consultation with a urologist and neurologist, the patient was immediately given intramuscular vitamin B1 at a dosage of 200 mg/day. After three days of supplementing with vitamin B1, her urinary incontinence and mental symptoms improved and were completely resolved after seven days of treatment. Surgeons should be aware that when long-term fasting patients have urinary incontinence, it may be a symptom of WE, and they should be supplied with vitamin B1 in a timely manner without extensive examination.